Sacrococcygeal teratoma: Atypical presentations in two neonates - Naina Bagrodia; Erica M. Carlisle; Grace Z. Mak (Elsevier, 2018)
The etiology of sacral masses in neonates is highly variable. The differential diagnosis includes sacrococcygeal teratoma (SCT), meningocele, myelomeningocele, rectal abscess, lymphangioma, hemangioma, lipoma, perineal cyst, bladder neck obstruction, imperforate anus, and rectal prolapse. Not only are there numerous pathologies in the differential diagnosis but also each entity can present in a classic or atypical manner. As the atypical presentations of these pathologies can create a confusing clinical picture, one must have a high index of suspicion and include the entire differential diagnosis when evaluating patients with perineal masses. A combination of history and physical examination, laboratory analysis, as well as pre- and postnatal imaging can help provide clarity about the patient's diagnosis. In this report, we present the work-up, diagnosis, and treatment of two neonates with perineal masses and atypical presentations of SCTs. Keywords: Sacrococcygeal teratoma, Neonate, Atypical presentation, Perineal mass